Glass composition and glass fiber for core material of vacuum heat insulation material

By adjusting the proportion of alkali metals in the glass and adding Al2O3 and B2O3 to regulate the glass network structure, the problem that existing glass compositions cannot reduce thermal conductivity is solved, and low thermal conductivity and good molding performance are achieved.

CN119430663APending Publication Date: 2025-02-14PANASONIC APPLIANCES (CHINA) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411361355.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing glass compositions used in vacuum insulating cores cannot reduce thermal conductivity without increasing molding difficulty or reducing fiber hardness.

Method used

By adjusting the ratio of monovalent alkali metal and divalent alkali metal in glass, especially the ratio of K2O/(Na2O+K2O) is 14-39%, and the ratio of CaO/(CaO+MgO) is 13%-37%, to Achieve low thermal conductivity of glass. At the same time, Al2O3 and B2O3 were added to further regulate the structure of the glass network.

Benefits of technology

It realizes that the thermal conductivity of glass is reduced without increasing the formation difficulty and fiber hardness, and the thermal conductivity of glass blocks does not exceed 0.880W/m/K, and the glass conversion temperature is lower than 570℃, satisfying vacuum insulation. board performance requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430663A_ABST
    Figure CN119430663A_ABST
Patent Text Reader

Abstract

The invention discloses a glass composition for a core material of a vacuum heat insulation material, which comprises the following components in percentage by mass: 14-39% of K2O / (Na2O + K2O) in monovalent alkali metal, 13-37% of CaO / (CaO + MgO) in divalent alkali metal and 57-73% of total monovalent alkali metal / total alkali metal. By regulating and controlling the network modifier oxide and regulating and controlling the polymerization degree and the connection degree of the glass network structure, the lowest level of heat conductivity can be achieved on the basis of not changing classic glass components, meanwhile, the processing technology of the glass is not influenced, and the strength of the glass fiber is not reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of glass compositions, and in particular to a glass composition and glass fiber used as a core material of a vacuum insulation material. Background Art

[0002] With the continuous progress of society, the importance of energy to economic development has also been highlighted. In order to reduce energy consumption, vacuum insulation panels (VIPs) as ultra-high performance insulation materials have gradually been valued. According to the definition of ASTMC1484-10, vacuum insulation panels are super insulation materials with a thermal conductivity of less than 11.5mW / mK. It is mainly composed of three parts: insulation core material, film material wrapping the core material, and getter. The core material is to ensure that the vacuum insulation panel has a certain strength to resist the influence of the internal and external atmospheric pressure difference; the film material wrapping the core material is to maintain the vacuum degree inside the vacuum insulation panel; the getter is to absorb and remove other gases that enter the vacuum insulation panel due to long-term use. Using glass fiber as the core material is the material that can achieve the lowest thermal conductivity among the commonly used core materials known to date. As a continuum in a vacuum environment, heat conduction in the vacuum insulation panel mainly relies on solid conduction, so the thermal conductivity of the core material prepared by glass fiber can greatly affect the thermal conductivity of the vacuum insulation panel. .

[0003] The glass formula corresponding to ordinary glass fiber includes: Network forming body composition: SiO 2 、Al 2 O 3 , B 2 O 5 Network modifier components: monovalent alkali metal (Na 2 O.K 2 O) and divalent alkali metals (CaO, MgO). Among them, the commonly used alkali metal ratio is 62.5-65.5% SiO2; 1.0-5.2% Al 2 O 3 ; 3.5-8.5% B 2 O 3 ;8-20% Na 2 O+K 2 O; 5.8-11.7% CaO+MgO; of which K 2 O / (Na2O+K 2 O) is 4-8%, the ratio of CaO / (CaO+MgO) in divalent alkali metals is 60%-75%, and the corresponding thermal conductivity of commonly used glass is 0.910-0.930W / m / K.

[0004] In actual R&D projects, the following limitations need to be considered simultaneously: 1) Reduce the thermal conductivity of glass, which is characterized by a decrease in the thermal conductivity of the glass block. As a continuum in a vacuum environment, the thermal conductivity of glass fiber can greatly affect the thermal conductivity of the vacuum insulation panel. (The thermal conductivity of glass blocks with ordinary glass formula is about 0.925W / m / K). 2) Glass fiber molding is easy, and the test is characterized by an increase in the glass transition temperature of the glass block by <10°C. The existing glass fiber production process is usually a pool kiln method, also known as wet molding. The molding process is mainly a high-temperature melting reaction of raw materials to form a homogeneous glass liquid, which is then cured by drawing to form glass fibers. In the production process of ordinary glass, the temperature of the pool kiln needs to reach about 1450°C to ensure the full reaction and homogenization of the raw materials. This process consumes a lot of energy, and the commonly used pool kiln can withstand a temperature of about 1600°C. If the melting temperature of the glass increases, the energy consumption, process and equipment losses of production will increase significantly. (The glass transition temperature of glass blocks with ordinary glass formula is about 546°C). 3) The hardness of the glass fiber does not decrease substantially, and the test shows that the elastic modulus of the glass block is not less than that of ordinary glass. Since heat conduction in vacuum insulation panels mainly relies on solid conduction, the three-dimensional spatial structure constructed by the core material made of glass fiber plays a decisive role in the final thermal conductivity of the product. Therefore, if the hardness of the glass fiber is reduced, the thermal conductivity of the finished product will decrease due to the inability to construct a three-dimensional structure. (The elastic modulus of a glass block with an ordinary glass formula is about 72GPa). For example, existing non-ordinary glass formulas, such as pure Na 2 O No K 2 Although the thermal conductivity of O glass is low (0.817 W / m / K), the glass transition temperature increases sharply (622°C). 2 The addition of new ingredients can significantly reduce the thermal conductivity of glass (0.782W / m / K), but in addition to the obvious increase in cost (the cost of TeO2 raw materials is about 700 yuan / kg), the glass transition temperature will also increase partially (573℃). At the same time, during production, the addition of new ingredients will increase the cost of washing materials in the next production line, reduce production efficiency, and thus lead to production costs. In summary, the existing glass compositions used for vacuum insulation core materials cannot reduce thermal conductivity without increasing the difficulty of molding and reducing the hardness of the fiber. Summary of the invention

[0005] In order to overcome the above-mentioned shortcomings of the glass composition used for the core material of vacuum insulation materials in the prior art that the thermal conductivity cannot be reduced without increasing the difficulty of molding and reducing the hardness of the fiber, the present invention provides a glass composition for the core material of vacuum insulation materials, which has the advantages of reducing the thermal conductivity without increasing the difficulty of molding and reducing the hardness of the fiber.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A glass composition for a vacuum insulation core material, wherein, by mass percentage, the ratio of K2O / (Na2O+K2O) in monovalent alkali metals is 14-39%, the ratio of CaO / (CaO+MgO) in divalent alkali metals is 13%-37%, and the overall ratio of monovalent alkali metals / total alkali metals is 57-73%.

[0008] As a preferred embodiment, the glass composition for the core material of the vacuum insulation material further comprises Al 2 O 3 , its Al 2 O 3 The mass percentage is 0.5-5.2%.

[0009] Preferably, the glass composition for the core material of the vacuum insulation material further comprises B 2 O3, its B 2 O 3 The mass percentage is 3.5-8.5%.

[0010] Preferably, the mass percentage of Na2O+K2O is 17.0-22.0%; and / or the mass percentage of CaO+MgO is 8.0-13.0%.

[0011] Preferably, the glass composition for the core material of the vacuum insulation material further comprises 62.5-65.5% SiO 2 .

[0012] Preferably, the K 2 The mass percentage of O is 2.3-8.2%.

[0013] Preferably, the mass percentage of CaO is 1.0-3.5%.

[0014] Preferably, the elastic modulus of the glass composition is not less than 72 GPa, the thermal conductivity of a glass block formed from the glass composition is not more than 0.880 W / m / K, and the glass transition temperature of the glass composition is lower than 570°C.

[0015] The present invention also discloses a glass fiber, which is formed by the glass composition for the core material of the vacuum insulation material.

[0016] The present invention also discloses a composite material, which is obtained by combining one or more organic and / or inorganic materials with glass fibers, wherein the glass fibers are formed by the above-mentioned glass composition for the core material of the vacuum insulation material.

[0017] The beneficial effects of the present invention are: (1) The present invention utilizes an important phenomenon in glass called the "mixed cation effect", that is, the interaction and influence of different cations in the glass. The interaction of cations will affect the network structure of the glass, thereby changing the thermal and physical properties. The interaction of different cations causes the change in the performance of the glass structure to be nonlinear. The glass former is the main body constituting the glass structure. The oxides of the glass former are interconnected through tetrahedral structural units to form a three-dimensional network, which is the key to giving the glass physical and chemical properties. Therefore, the glass former components have a significant impact on the glass transition temperature Tg, melt viscosity-temperature characteristics and mechanical properties, and cannot meet the requirements of not increasing the difficulty of molding and not reducing the hardness of the fiber. In the present invention, the glass former components are not adjusted, but the network modifier is changed. Alkali metal oxides (Na 2 O.K 2 O) and alkaline earth metal oxides (CaO, MgO), mainly play the role of network modifiers in the glass structure. The low thermal conductivity of glass is due to the interference of atomic vibrations in the amorphous network. The structure of glass is disordered and irregular. The disordered structure of glass leads to a weak contribution of phonon propagation to thermal conductivity, while the degree of polymerization of the glass network has a greater influence on the microscopic conduction of heat.

[0018] (2) The present invention can reduce the Tg temperature of glass and the melting temperature by adding the network modifier oxide. The present invention can achieve the lowest level of thermal conductivity without changing the classic glass composition by regulating the network modifier oxide and regulating the degree of polymerization and connection of the glass network structure, while not affecting the glass processing technology and not reducing the strength of the glass fiber.

[0019] (3) The present invention can achieve regulation of the thermal conductivity of glass by regulating the degree of polymerization and connection of the glass network structure.

[0020] (4) According to the formula parameters provided by the invention, the thermal conductivity of the glass block formed by the glass composition does not exceed 0.880 W / m / K. Compared with the glass block of the common glass composition, the thermal conductivity can be reduced by 4%-9%. At the same time, the glass transition temperature of the glass block of the present invention does not exceed 570°C, and still has good molding performance. The elastic modulus is not less than 72 GPa, which does not affect the strength of the glass fiber. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a table showing the formula components and performance data of glass composition embodiments 1-6 of the present invention. DETAILED DESCRIPTION

[0022] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0023] The present invention substantially does not contain Li2O, BaO, ZnO, PbO and other components. “Substantially does not contain” means that these components are impurities and are not artificially added, but may be introduced in small amounts by mineral raw materials in the form of impurities. The mass content of a single component generally does not exceed 0.1%.

[0024] The content of each component in the present invention is a mass percentage, specifically referring to the percentage of the mass of a certain substance in the mixture to the total mass. Figure 1 In the table, the current formula composition is the glass block test result generated by the glass formula for vacuum insulation panels sold on the market, and the numerical value is the mass percentage. Due to factors such as detection error, trace impurities not analyzed and included, and decimal values, the total percentage content of the components described in the table may not reach 100%. The glass fiber in the present invention is made by a well-known wet molding process, and can also be made by a dry molding process.

[0025] In the present invention, Na 2 O+K 2 O and CaO+MgO both refer to the sum of two independent components. 2 O / (Na 2 O+K 2 The percentage of the ratio of CaO / (CaO+MgO) and the ratio of CaO / (CaO+MgO) refers to the K content of the independent monovalent base. 2 O is the percentage of the entire monovalent base and CaO in the divalent base is the percentage of the entire divalent base, not the percentage of the total substance.

[0026] Thermal conductivity test method in the present invention: GB / T10297-2015 Determination of thermal conductivity of non-metallic solid materials - hot wire method: TPS-2500S thermal constant analyzer. GB / T16920-2015 Determination of average linear thermal expansion coefficient of glass: Netzsch DIL402PC thermal expansion instrument.

[0027] Example 1: A glass composition for a vacuum insulation material core material, used for drawing to form glass fibers, the composition comprising the following components: 64.47% SiO 2 ; 1.71% Al 2 O 3 5.17% of B 2 O 3 ;19.98% Na 2 O+K 2 O; 5.50% K 2 O; 8.42% CaO + MgO. Among them, 1.13% CaO. Among the monovalent alkali metals, K 2 O / (Na 2 O+K 2The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 28%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 13%, and the ratio of monovalent alkali metal / total alkali metal is 70%. The elastic modulus of the glass composition is 75.59 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.845 W / m / K. The glass transition temperature of the glass composition is 549°C.

[0028] Example 2: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 64.20% SiO 2 ; 1.70% Al 2 O 3 5.14% of B 2 O 3 ; 5.56% K 2 O, 20.16% Na 2 O+K 2 O; 8.53% CaO + MgO, of which 2.20% CaO; among the monovalent alkali metals, K 2 O / (Na 2 O+K 2 The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 28%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 26%, while the ratio of monovalent alkali metal / total alkali metal is 70%. The elastic modulus of the glass composition is 77.83 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.853 W / m / K. The glass transition temperature of the glass composition is 550°C.

[0029] Example 3: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 63.87% SiO 2 ; 1.69% Al 2 O 3 5.12% B 2 O 3 ; 8.17% K 2 O, 20.72% Na 2 O+K 2 O; 8.34% CaO + MgO, of which 1.12% CaO; among the monovalent alkali metals, K 2 O / (Na 2 O+K 2 The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 39%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 13%, while the ratio of monovalent alkali metal / total alkali metal is 71%. The elastic modulus of the glass composition is 76 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.861 W / m / K. The glass transition temperature of the glass composition is 553°C.

[0030] Example 4: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 63.47% SiO 2 ; 1.68% Al 2 O 3 5.09% B 2 O 3 ; 8.12% K 2 O, 20.59% Na 2 O+K 2 O; 8.91% CaO + MgO, of which 3.33% CaO; among the monovalent alkali metals, K 2 O / (Na 2 O+K 2 The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 39%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 37%, while the ratio of monovalent alkali metal / total alkali metal is 70%. The elastic modulus of the glass composition is 75 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.870 W / m / K. The glass transition temperature of the glass composition is 554°C.

[0031] Example 5: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 64.66% SiO 2 ; 1.71% Al 2 O 3 4.7% of B 2 O 3 ;19.09% Na 2 O+K 2 O; 2.76% of K 2 O, 9.08% CaO + MgO, of which 3.39% is CaO; among the monovalent alkali metals, K 2 O / (Na 2 O+K 2 The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 14%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 37%, while the ratio of monovalent alkali metal / total alkali metal is 68%. The elastic modulus of the glass composition is 76.31 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.868 W / m / K. The glass transition temperature of the glass composition is 551°C.

[0032] Example 6: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 65.08% SiO 2 ; 1.73% Al 2 O 35.21% of B 2 O 3 ;19.22% Na 2 O+K 2 O; 2.78% of K 2 O, 8.5% CaO + MgO, of which 1.14% is CaO; among the monovalent alkali metals, K 2 O / (Na 2 O+K 2 The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 14%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 13%, while the ratio of monovalent alkali metal / total alkali metal is 68%. The elastic modulus of the glass composition is 74.25 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.872 W / m / K. The glass transition temperature of the glass composition is 548°C.

[0033] Example 7: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 63.5% SiO 2 ; 1.63% Al 2 O 3 4.91% of B 2 O 3 ;17% Na 2 O+K 2 O, of which 2.30% K 2 O; 13.00% CaO + MgO, of which 1.70% CaO; among the monovalent alkali metals, K 2 O / (Na 2 O+K 2 The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 14%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 13%, while the ratio of monovalent alkali metal / total alkali metal is 57%. The elastic modulus of the glass composition is 76.57 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.877 W / m / K. The glass transition temperature of the glass composition is 557°C.

[0034] Example 8: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 65.5% SiO 2 ; 0.65% Al 2 O 3 4.31% of B 2 O 3 ;21.17% Na 2 O+K 2 O, of which 8.20% K 2O; 8.03% CaO + MgO, of which 2.97% CaO; among the monovalent alkali metals, K 2 O / (Na 2 O+K 2 The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 39%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 37%, while the ratio of monovalent alkali metal / total alkali metal is 73%. The elastic modulus of the glass composition is 72.17 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.865 W / m / K. The glass transition temperature of the glass composition is 564°C.

[0035] Example 9: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 62.5% SiO 2 ; 5.2% Al 2 O 3 ; 3.5% B 2 O 3 ;17.12% Na 2 O+K 2 O, of which 5.56% K 2 O; 11.46% CaO + MgO, of which 3.5% CaO; among the monovalent alkali metals, K 2 O / (Na 2 O+K 2 The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 32%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 31%, while the ratio of monovalent alkali metal / total alkali metal is 60%. The elastic modulus of the glass composition is 76.35 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.861 W / m / K. The glass transition temperature of the glass composition is 561°C.

[0036] Example 10: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 62.5% SiO 2 ; 0.55% Al 2 O 3 8.41% of B 2 O 3 ;20.40% Na 2 O+K 2 , where K 2 O is 3.50%; 8.17% CaO+MgO, CaO is 1.06%; among the monovalent alkali metals, K 2 O / (Na 2 O+K 2The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 17%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 13%, while the ratio of monovalent alkali metal / total alkali metal is 71%. The elastic modulus of the glass composition is 72.41 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.857 W / m / K. The glass transition temperature of the glass composition is 567°C.

[0037] Embodiment 11: The present invention also discloses a glass fiber, which is formed from a glass composition for a core material of a vacuum insulation material. The glass composition for a core material of a vacuum insulation material is used for drawing to form a glass fiber.

[0038] Example 12: The present invention also discloses a composite material, which is obtained by combining one or more organic and / or inorganic materials with glass fibers, wherein the glass fibers are formed by a glass composition used for the core material of a vacuum insulation material.

[0039] Comparative Example 1: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 65.34% SiO 2 ; 1.73% Al 2 O 3 5.24% of B 2 O 3 ;18.57% Na 2 O+K 2 O; 17.90% of K 2 O; 8.85% CaO + MgO. Of which 2.28% is CaO. Of which K 2 O / (Na 2 O+K 2 The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 4%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 26%, while the ratio of monovalent alkali metal / total alkali metal is 68%. The elastic modulus of the glass composition is 69.57 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.897 W / m / K. The glass transition temperature of the glass composition is 559°C.

[0040] Comparative Example 2: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 63.08% SiO 2 ; 1.67% Al 2 O 3 5.05% B 2 O 3 ;21.39% Na 2 O+K 2 O; 10.62% of K 2O; 8.55% CaO + MgO, of which 2.20% is CaO. Among the monovalent alkali metals, K 2 O / (Na 2 O+K 2 The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 50%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 26%, while the ratio of monovalent alkali metal / total alkali metal is 71%. The elastic modulus of the glass composition is 73.28 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.915 W / m / K. The glass transition temperature of the glass composition is 557°C.

[0041] Comparative Example 3: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 64.93% SiO 2 ; 1.72% Al 2 O 3 ; 5.20% B 2 O 3 ;18.45% Na 2 O+K 2 O; 17.79% of K 2 O; 9.43% CaO + MgO, of which 4.54% is CaO. Among the monovalent alkali metals, K 2 O / (Na 2 O+K 2 The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 4%, and the ratio of monovalent alkali metal / total alkali metal is 66%. The elastic modulus of the glass composition is 72.04 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.929 W / m / K. The glass transition temperature of the glass composition is 553°C.

[0042] Comparative Example 4: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 63.45% SiO 2 ; 1.68% Al 2 O 3 5.08% B 2 O 3 ;14.52% Na 2 O+K 2 O; 14.25% of K 2 O; 9.85% CaO + MgO, of which 6.69% is CaO. Among the monovalent alkali metals, K 2 O / (Na 2 O+K 2The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 28%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 68%, while the ratio of monovalent alkali metal / total alkali metal is 67%. The elastic modulus of the glass composition is 74.03 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.919 W / m / K. The glass transition temperature of the glass composition is 550°C.

[0043] Comparative Example 5: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 61.93% SiO 2 ; 1.64% Al 2 O 3 4.96% of B 2 O 3 ;29.16% Na 2 O+K 2 O; 21.14% of K 2 O; 2.06% CaO + MgO, of which 0.53% is CaO. Among the monovalent alkali metals, K 2 O / (Na 2 O+K 2 The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 28%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 26%, while the ratio of monovalent alkali metal / total alkali metal is 93%. The elastic modulus of the glass composition is 73.66 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.901 W / m / K. The glass transition temperature of the glass composition is 493°C.

[0044] Comparative Example 6: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 63.42% SiO 2 ; 1.68% Al 2 O 3 5.08% B 2 O 3 ;23.23% Na 2 O+K 2 O; 16.83% of K 2 O; 6.32% CaO + MgO, of which 1.63% is CaO. Among the monovalent alkali metals, K 2 O / (Na 2 O+K 2The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 28%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 26%, while the ratio of monovalent alkali metal / total alkali metal is 79%. The elastic modulus of the glass composition is 74.96 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.946 W / m / K. The glass transition temperature of the glass composition is 547°C.

[0045] Comparative Example 7: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 62.30% SiO 2 ; 1.65% Al 2 O 3 ; 4.99% B 2 O 3 ;21.12% Na 2 O+K 2 O; 10.49% of K 2 O; 9.68% CaO + MgO, of which 6.57% is CaO. Among the monovalent alkali metals, K 2 O / (Na 2 O+K 2 The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 50%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 68%, while the ratio of monovalent alkali metal / total alkali metal is 69%. The elastic modulus of the glass composition is 74.51 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.898 W / m / K. The glass transition temperature of the glass composition is 549°C.

[0046] Comparative Example 8: A glass composition for vacuum insulation core material, used for drawing to form glass fiber, the composition comprising the following components: 59.78% SiO 2 ; 1.58% Al 2 O 3 4.79% of B 2 O 3 ;25.50% Na 2 O+K 2 O; 0% K 2 O; 8.10% CaO + MgO, of which 2.09% is CaO. Among the monovalent alkali metals, K 2 O / (Na 2 O+K 2 The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 100%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 26%, while the ratio of monovalent alkali metal / total alkali metal is 76%. The elastic modulus of the glass composition is 65.86 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.817 W / m / K. The glass transition temperature of the glass composition is 622°C.

[0047] Comparative Example 9: A glass composition for vacuum insulation core material currently available on the market is used for drawing to form glass fiber, and the composition comprises the following components: 64.50% SiO 2 ; 1.71% Al 2 O 3 5.17% of B 2 O 3 ;18.33% Na 2 O+K 2 O; 0.66% of K 2 O; 10.01% CaO + MgO. Of which 6.79% is CaO. Of which K 2 O / (Na 2 O+K 2 The ratio of CaO / (CaO+MgO) in the divalent alkali metal is 4%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 68%, while the ratio of monovalent alkali metal / total alkali metal is 65%. The elastic modulus of the glass composition is 72.08 GPa. The thermal conductivity of the glass block formed by the glass composition is 0.925 W / m / K. The glass transition temperature of the glass composition is 546°C.

[0048] By comparing the experimental data of the above embodiments 1 to 10 with the experimental data of the glass composition for the core material of vacuum insulation material currently on the market in comparative example 9, it can be seen that the present application simultaneously satisfies the three conditions that the elastic modulus of the glass composition is not less than 72GPa. The thermal conductivity of the glass block formed by the glass composition does not exceed 0.880W / m / K. The glass transition temperature of the glass composition is lower than 570°C. However, the thermal conductivity of the glass block of the glass composition in the prior art exceeds 0.88W / m / K. By comparing the experimental data of the above embodiments 1 to 10 with the experimental data of comparative examples 1 to 8, it can be seen that the three sets of data of the elastic modulus, glass transition temperature and thermal conductivity of the glass block of the comparative example beyond the process range of right 1 cannot simultaneously meet the above preset requirements.

[0049] The above description is only a preferred embodiment of the present invention, and does not limit the patent protection scope of the present invention. Any equivalent structural transformation made by using the contents of the present invention and the drawings, directly or indirectly used in other related technical fields, is also included in the protection scope of the present invention.

Claims

1. A glass composition for a core material of a vacuum insulation material, characterized in that: In terms of mass percentage, the ratio of K2O / (Na2O+K2O) in the monovalent alkali metal is 14-39%, and the ratio of CaO / (CaO+MgO) in the divalent alkali metal is 13%-37%, and the overall monovalent alkali metal / total alkali metal ratio is 57-73%.

2. The glass composition for vacuum insulation core material according to claim 1, characterized in that: The mass percentage of Na2O+K2O is 17.0-22.0%; and / or the mass percentage of CaO+MgO is 8.0-13.0%.

3. The glass composition for a core material of a vacuum insulation material according to claim 1, characterized in that: The mass percentage of K2O is 2.3-8.2%.

4. The glass composition for a core material of a vacuum insulation material according to claim 1, characterized in that: The mass percentage of CaO is 1.0-3.5%.

5. The glass composition for a core material of a vacuum insulation material according to claim 1, characterized in that: It also includes Al2O3, and the mass percentage of Al2O3 is 0.5-5.2%.

6. The glass composition for a core material of a vacuum insulation material according to claim 1, characterized in that: It also includes B2O3, and the mass percentage of B2O3 is 3.5-8.5%.

7. The glass composition for a core material of a vacuum insulation material according to claim 1, characterized in that: It also includes 62.5-65.5% SiO2.

8. A glass composition for a core material of a vacuum insulation material according to claim 1 or 2 or 3 or 4 or 5 or 6 or 7, characterized in that: The elastic modulus of the glass composition is not less than 72 GPa, the thermal conductivity of a glass block formed by the glass composition is not more than 0.880 W / m / K, and the glass transition temperature of the glass composition is lower than 570°C.

9. A glass fiber, characterized in that: The glass composition for a core material of a vacuum insulation material according to any one of claims 1 to 8 is formed.